2017
DOI: 10.1002/lary.27060
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected prominent tension pneumosella five years after endoscopic endonasal transsphenoidal surgery

Abstract: Tension pneumosella (TP) is a rare entity reported as the invagination of the sphenoid sinus mucosa into the skull base after endonasal transsphenoidal surgery. Few studies have reported on TP, and in these studies, invagination is confined to either the intrasellar or suprasellar area. We encountered a case of unexpected prominent TP toward the intracranial space 5 years after endoscopic endonasal transsphenoidal surgery (EETS) for a nonfunctioning pituitary adenoma. In addition, we present a hypothesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…TP following skull base surgery is a rare complication, previously reported to have only been reported in 33 cases in the literature, [1][2][3]6,7,14,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] including this case (Table 1). Iatrogenic injury has been reported as a cause of TP during skull base surgery.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…TP following skull base surgery is a rare complication, previously reported to have only been reported in 33 cases in the literature, [1][2][3]6,7,14,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] including this case (Table 1). Iatrogenic injury has been reported as a cause of TP during skull base surgery.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…Eighteen articles were identified using the search strategy outlined above in the study design and literature review. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The earliest report from this search was a single case report published in 1994. 3 Including the four cases from our institutions described above, a total of 26 cases were included in the review (Table 1) For the treatment of TP, endoscopic multilayer closure of the skull base defect was performed in 13 patients, cranial burr hole surgery in two, cranial burr hole surgery and endoscopic multilayer closure of the skull base defect in five, and bifrontal craniotomy to repair the defect in the skull base in two patients.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, Matsuda et al reported that one patient unexpectedly incurred prominent TP 5 years after endoscopic endonasal trans-sphenoidal surgery for pituitary adenoma. 12 Therefore, it is crucial that otolaryngologists and neurosurgeons understand that TP may also occur many years after endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of postoperative diaphragmatic defects was found to be of great significance in avoiding complications [15]. In addition, even if immediate postoperative pneumocephalus can be avoided by simple repair of diaphragmatic defects, some authors advocate the need for rigid reconstruction with septal cartilage or a titanium plate to prevent invagination of the sphenoid mucosa [23,24]. Pneumocephalus can develop in the sella floor; there is a report of tension pneumosella occurring five years after endoscopic endonasal transsphenoidal surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, even if immediate postoperative pneumocephalus can be avoided by simple repair of diaphragmatic defects, some authors advocate the need for rigid reconstruction with septal cartilage or a titanium plate to prevent invagination of the sphenoid mucosa [23,24]. Pneumocephalus can develop in the sella floor; there is a report of tension pneumosella occurring five years after endoscopic endonasal transsphenoidal surgery [24]. Consequently, CSF leaks with persistent PNC could bear greater risks than simple CSF leaks [13,19].…”
Section: Discussionmentioning
confidence: 99%